Child Protection in Indonesian Islamic Boarding Schools: Between Compliance and Normative Coherence. A Systematic Literature Review - Achmad Muzammil Alfan Nasrullah; Mohammad Muchlis Solichin; Siswanto Siswanto (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2026)
Child protection in Indonesian pesantren remains structurally compromised by a normative gap between Islamic legal principles and state regulatory instruments, a gap distinct from mere enforcement failure. This systematic review synthesizes existing scholarship on this tension and proposes an integrative analytical framework grounded in maqāṣid al-sharīʻah. Following the PRISMA 2020 protocol, 51 peer-reviewed articles (2014–2025) were retrieved from Scopus, Web of Science, ERIC, and Dimensions and analyzed using a hybrid thematic-framework synthesis informed by Jasser Auda's systems approach to maqāṣid. Three disconnected literature streams were identified: empirical-structural studies documenting violence, compliance-oriented assessments of regulatory adherence, and maqāṣid-doctrinal analyses confined to family law, none of which integrates all three within the pesantren context. Applying a four-domain normative gap rubric to taʻzīr legitimacy, reporting mechanisms, kiai–santri power relations, and disciplinary boundaries, a composite gap score of 9.75/12 was obtained relative to Perdirjen 1262/2024, indicating a critical coherence deficit. The Beyond Compliance framework proposed here operates at three recursive levels, normative, institutional, and evaluative, arguing that effective child protection requires principled coherence between Islamic law and state regulation, not compliance with the latter alone. This constitutes the First PRISMA-based systematic review in internationally indexed databases that integrates maqāṣid al-sharīʻah with pesantren child protection scholarship, and the first peer-reviewed evaluation of Perdirjen 1262/2024. Findings carry direct implications for pesantren policy reform and Islamic jurisprudence on child welfare